Comparison of changes in stress coping strategies between cognitive behavioral therapy and pharmacotherapy - Ihara, Sakae; Katayama, Nariko; Nogami, Waka; Amano, Mizuki; Noda, Sachiko; Kurata, Chika; Kobayashi, Yuki; Sasaki, Yohei; Mitsuda, Dai; Ozawa, Mire; Matsuoka, Jun; Takemura, Ryo; et al. (Frontiers in Psychiatry, 2024)
Coping refers to conscious responses to negative circumstances, with the intention of ameliorating these situations. Few studies have compared the differences between psychotherapy and medication treatment for coping strategies for depression. In this study, we investigated the differences in coping strategies between cognitive behavioral therapy (CBT) combined with medication (CBT group) and medication alone (pharmacotherapy group) among outpatients with depression.A prospective observational study was conducted among 50 patients with major depression (24 and 26 in the CBT and pharmacotherapy groups, respectively). Stress coping strategies (Coping Inventory for Stressful Situations [CISS]) and depression severity (Beck Depression Inventory-Second Edition [BDI-II]) were assessed at baseline and 16 weeks later. Changes in the CISS and BDI-II scores in both groups were tested using repeated analysis of variance. Inverse probability weighting with propensity score analysis was applied to address potential selection bias.At 16 weeks, the CBT group exhibited increased CISS task-oriented coping, distraction, and social diversion scores, which differed from those of the pharmacotherapy group. The CBT group exhibited a significantly greater reduction in depressive symptoms than the pharmacotherapy group.This study was not a randomized controlled trial and thus may have selection bias.Gaining adaptive coping skills, including task-oriented coping, distraction, and social diversion skills, by combining CBT with medication may lead to greater improvement in depression symptoms. These findings suggest that clinicians should evaluate coping strategies and facilitate the acquisition of adaptive coping strategies in patients with depression to reduce their symptoms.コメントの追加 [A1]: Kindly note that a study having several limitations could be perceived as negative by the reviewers of journal. Kindly consider revising this to lend a more euphemistic tone to the text.